Prevalence and pattern of skin disorders among children living in orphanages in Fayoum and Giza governorates, Egypt - Noha Ezzat Mohamed; Wafaa Yousif Abdel-Wahed; Shimaa Mohammed Gomaa; Mai Ashraf Hosny (Tropical Medicine and Health)
Abstract Background Childhood is a crucial period that shapes a person’s growth and development. For orphans, a lack of familial support affects their upbringing, making orphanages crucial for care. Children living in orphanage centers are vulnerable to several conditions, including dermatological disorders, due to factors such as malnutrition, overcrowding, and poor hygiene. The current study was carried to determine the prevalence and patterns of skin disorders among orphan children in Egypt, and to identify associated risk factors among orphans in Egypt. Methods A cross-sectional study was conducted among 415 children aged 1–18 years living in orphanage centers in Fayoum and Giza governorates, Egypt. Results Among the children, 77.1% had at least one skin disorder, with noninfectious conditions being more prevalent than infectious conditions (67.4 vs. 24.3%). The most common noninfectious conditions were dermatitis/eczema, pigmentary disorders, skin appendage disorders, and psycho-cutaneous issues. Fungal infections were the most common infectious condition. There was a significant relationship between hygiene and the type of skin disorder. Conclusion The prevalence of skin diseases in orphanages in Egypt is relatively high and is dominated by noninfectious skin diseases, and the prevalence of psycho-cutaneous disorders is high among these children. Comprehensive care strategies focusing on improving hygiene and emotional support and preventing abuse are essential for reducing the incidence of skin disorders and enhancing the overall health of orphaned children.